2019
DOI: 10.1002/pen.25240
|View full text |Cite
|
Sign up to set email alerts
|

Profile Extrusion: Experimental Assessment of a Numerical Code to Model the Temperature Evolution in the Cooling/Calibration Stage

Abstract: Designing an industrial calibration system that ensures fast and uniform cooling of a complex extruded profile is always a difficult task. Numerical tools are a valuable aid for the design of these systems in order to achieve fast, low‐cost, and effective solutions. This work comprises the experimental validation of a numerical code, previously developed to support the design of profile extrusion calibration systems, using data collected from an industrial extrusion line. The referred numerical code was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Commonly used approaches to study polymers’ effects on material extrusion manufacturing processes are both theoretical (e.g. numerical calculations) [ 20 , 21 , 22 ] and experimental methodologies [ 23 , 24 , 25 , 26 ]. For the analysis of the results various modeling tools are often used, such as the Taguchi design [ 3 , 8 , 9 , 15 , 16 , 17 , 19 ], full factorial Design of Experiments [ 27 , 28 ], Box-Behnken design [ 13 ], Analysis of Variances (ANOVA) [ 11 , 29 , 30 ], and artificial neural networks modeling [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used approaches to study polymers’ effects on material extrusion manufacturing processes are both theoretical (e.g. numerical calculations) [ 20 , 21 , 22 ] and experimental methodologies [ 23 , 24 , 25 , 26 ]. For the analysis of the results various modeling tools are often used, such as the Taguchi design [ 3 , 8 , 9 , 15 , 16 , 17 , 19 ], full factorial Design of Experiments [ 27 , 28 ], Box-Behnken design [ 13 ], Analysis of Variances (ANOVA) [ 11 , 29 , 30 ], and artificial neural networks modeling [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] and Rajkumar et al. [ 21 ] modeled the heat transfer in the cooling stage using a numerical finite volume method. They found that it was more efficient to use several individual cooling units in series, separated by relatively short air zones where the temperature tends to equalize.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, temperature gradients along the profile contour and thickness should be minimized, in order to induce adequate morphology development and a reduced level of residual thermal stresses. [17][18][19] Nóbrega et al [20] and Rajkumar et al [21] modeled the heat transfer in the cooling stage using a numerical finite volume method. They found that it was more efficient to use several individual cooling units in series, separated by relatively short air zones where the temperature tends to equalize.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistency of temperature in extruder machine needs CST to stabilize the temperature in several zone. Several research found that designing cooling system in extruder machine to obtain uniform cooling and to produce complex extruded profile is challenging [6]. This system should also be able to produce a decreased degree of residual thermal stresses by limiting the temperature gradient that develops along the profile cross section [7,8].…”
Section: Introductionmentioning
confidence: 99%